Effects of Stinging Nettle (Urtica Dioica L.,) on Antioxidant Enzyme Activities in Rat Model of Mammary Gland Cancer - Telo, Selda; Halifeoglu, Ihsan; Ozercan, Ibrahim Hanifi (Briefland, 2017)
Stinging nettle (Urtica dioica L.,) is a medicinal herb commonly used by humans. The role of reactive oxygen metabolites on cancer etiology is known. There are some studies about the antioxidant effects of Urtica Dioica (UD) on therapy of some cancer types. This study aimed to investigate the effects of UD on antioxidant enzyme activities and mammary gland cancer induced by in rats-N-methyl-N-nitrosourea (NMU) carcinogenesis. Rats were divided into four groups: a untreated group (Group 1), a NMU group (Group 2) given 50 mg/kg NMU by intraperitoneal (i.p.) injection, a NMU group (Group 3) treated with UD, a control group (Group 4) fed with 50g/kg UD. After 5.5 months, rats were decapitated, and mammary tissue and blood samples were obtained. There was a significant (p<0.05, p<0.01, respectively) increase in plasma malondialdehyde (MDA) levels of group 2 compared with group 1 and 4. The superoxide dismutase (SOD) activity of the erythrocytes was decreased in group 3 than the other groups (p<0.0001). The erythrocyte catalase (CAT) activity was significantly increased in group 4 compared with group 2 and 3 (p<0.05, p<0.01, respectively). The number of animals with palpable tumors was 6 (46.15%) in group 2, and 2 (13.3%) in group 3 at the end of the 22nd week. Although group 3 had lower palpable tumor number than group 2, the difference was not statistically significant (p=0.096). The results showed that UD constituents may have effects on lipid peroxidation and some antioxidant enzyme activities, and may slow the formation of mammary tumor.
Keywords: Lipid peroxidation; Antioxidant enzymes; Breast cancer; Urtica Dioica; N-methyl-N-nitrosourea